Answered

Westonci.ca is the trusted Q&A platform where you can get reliable answers from a community of knowledgeable contributors. Discover a wealth of knowledge from professionals across various disciplines on our user-friendly Q&A platform. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.

In this question, you must show all stages of your working. Solutions relying on calculator technology are not acceptable.

(i) Given:
[tex]\[ f(x) = (x + \sqrt{2})^2 + (3x - 5\sqrt{8})^2 \][/tex]

Express [tex]\( f(x) \)[/tex] in the form [tex]\( ax^2 + bx\sqrt{2} + c \)[/tex] where [tex]\( a \)[/tex], [tex]\( b \)[/tex], and [tex]\( c \)[/tex] are integers to be found.


Sagot :

Alright, to express the function [tex]\( f(x) = (x + \sqrt{2})^2 + (3x - 5\sqrt{8})^2 \)[/tex] in the form [tex]\( ax^2 + bx\sqrt{2} + c \)[/tex], we need to expand each term and then combine them.

1. Expanding [tex]\((x + \sqrt{2})^2\)[/tex]:

Let's start with the first term [tex]\((x + \sqrt{2})^2\)[/tex].

[tex]\[ (x + \sqrt{2})^2 = x^2 + 2x\sqrt{2} + (\sqrt{2})^2 \][/tex]

Since [tex]\((\sqrt{2})^2 = 2\)[/tex], we have:

[tex]\[ (x + \sqrt{2})^2 = x^2 + 2x\sqrt{2} + 2 \][/tex]

2. Expanding [tex]\((3x - 5\sqrt{8})^2\)[/tex]:

Next, let's expand the second term [tex]\( (3x - 5\sqrt{8})^2 \)[/tex].

First, simplify [tex]\(5\sqrt{8}\)[/tex]. Note that [tex]\(\sqrt{8} = \sqrt{4 \cdot 2} = 2\sqrt{2}\)[/tex], so:

[tex]\[ 5\sqrt{8} = 5 \cdot 2\sqrt{2} = 10\sqrt{2} \][/tex]

Now, expand [tex]\( (3x - 10\sqrt{2})^2 \)[/tex]:

[tex]\[ (3x - 10\sqrt{2})^2 = (3x)^2 - 2 \cdot (3x) \cdot (10\sqrt{2}) + (10\sqrt{2})^2 \][/tex]

[tex]\[ = 9x^2 - 60x\sqrt{2} + 100 \cdot 2 \][/tex]

[tex]\[ = 9x^2 - 60x\sqrt{2} + 200 \][/tex]

3. Combining the expanded terms:

Now, we combine the expanded forms of the two terms:

[tex]\[ f(x) = (x^2 + 2x\sqrt{2} + 2) + (9x^2 - 60x\sqrt{2} + 200) \][/tex]

Combine like terms:

[tex]\[ f(x) = x^2 + 9x^2 + 2x\sqrt{2} - 60x\sqrt{2} + 2 + 200 \][/tex]

Simplify:

[tex]\[ f(x) = 10x^2 - 58x\sqrt{2} + 202 \][/tex]

Thus, expressed in the form [tex]\( ax^2 + bx\sqrt{2} + c \)[/tex], we have:

[tex]\[ a = 10 \][/tex]
[tex]\[ b = -58 \][/tex]
[tex]\[ c = 202 \][/tex]

So, the final expression is:

[tex]\[ f(x) = 10x^2 - 58x\sqrt{2} + 202 \][/tex]